New Temperature-Insensitive Electronically-Tunable Grounded Capacitor Simulator - Muhammad Taher Abuelma'atti; Muhammad Haroon Khan (Active and Passive Electronic Components)
A new circuit for simulating a grounded capacitor is presented. The circuit uses one operationalamplifier (OA), three operational-transconductance amplifiers (OTAs), and one capacitor. The realized capacitor is temperature-insensitive and electronically tunable. Experimental results are included.